Broad requirement for terminal sialic acid residues and FcγRIIB for the preventive and therapeutic activity of intravenous immunoglobulins in vivo. Issue 5 (7th March 2014) - Schwab, Inessa; Mihai, Sidonia; Seeling, Michaela; Kasperkiewicz, Michael; Ludwig, Ralf J.; Nimmerjahn, Falk
<x xml:space="preserve">Abstract</x> Intravenous immunoglobulin (IVIg) therapy is widely used to treat a variety of autoimmune diseases including immunothrombocytopenia, chronic inflammatory demyelinating polyneuropathy, and more recently autoimmune skin blistering diseases. Despite this well‐documented clinical success, the precise molecular and cellular mechanisms underlying this immunomodulatory activity are discussed controversially. In particular, the clinically relevant therapeutic pathway of IVIg‐mediated immune modulation has not been studied in detail. In the present study, we use four independent in vivo model systems of auto‐Ab‐mediated autoimmune disease to identify a common pathway explaining IVIg activity under therapeutic conditions in vivo. We show that irrespective of the in vivo model system, IVIg activity is strictly dependent on the presence of terminal sialic acid residues and the inhibitory FcγRIIB under preventive as well as therapeutic treatment conditions. In contrast, specific ICAM3 grabbing nonintegrin related 1, previously demonstrated to be essential under preventative treatment conditions, showed a disease‐specific impact on IVIg‐mediated resolution of established autoimmune disease.